A compound and its application
By using new compounds with azebenzoincinazole group structure as electron transport layer materials in OLED devices, the improvement space for existing OLED devices in terms of photoelectric performance and service life is solved, and the effects of high luminous efficiency and low starting voltage are achieved.
Patent Information
- Application Number
- CN201911149003.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-11-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2039-11-21
AI Technical Summary
There is still room for improvement in existing OLED devices in terms of photoelectric performance and service life, especially with challenges in low starting voltage and high luminous efficiency.
A new compound is adopted, whose structural characteristics include azabenzoincinazole group. The N atom on the benzene ring and the N of the indenazole group are not in ortho-position, and have good electron deficiency and planar structure, which improves electron injection and migration capabilities.
By using this compound as the electron transport layer material, the electron injection and migration efficiency of OLED devices is significantly improved, and the excellent effects of high luminescence efficiency and low starting voltage are achieved.
Smart Images

Figure BDA0002283013640000011 
Figure BDA0002283013640000031 
Figure BDA0002283013640000032
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic electroluminescence, and in particular to a compound and application thereof. Background Art
[0002] Organic electroluminescent (OLED: Organic Light Emission Diodes) devices are a type of device with a sandwich-like structure, including positive and negative electrode film layers and organic functional material layers sandwiched between the electrode film layers. When voltage is applied to the electrodes of the OLED device, positive charges are injected from the positive electrode and negative charges are injected from the negative electrode. Under the action of the electric field, the positive and negative charges migrate in the organic layer and meet to combine and emit light. Due to the advantages of high brightness, fast response, wide viewing angle, simple process, and flexibility, OLED devices have attracted much attention in the fields of new display technology and new lighting technology. At present, this technology has been widely used in display panels of new lighting fixtures, smart phones, tablet computers and other products, and will further expand to the application fields of large-size display products such as televisions. It is a new display technology with fast development and high technical requirements.
[0003] As OLED continues to advance in the two major fields of lighting and display, people are paying more attention to the research on its core materials. This is because an OLED device with good efficiency and long life is usually the result of an optimized combination of device structure and various organic materials, which provides great opportunities and challenges for chemists to design and develop functional materials of various structures. Common functional organic materials include: hole injection materials, hole transport materials, hole blocking materials, electron injection materials, electron transport materials, electron blocking materials, luminescent host materials and luminescent guests (dyes), etc.
[0004] In order to prepare OLED light-emitting devices with lower driving voltage, better luminous efficiency and longer device life, and to continuously improve the performance of OLED devices, it is necessary not only to innovate the structure and manufacturing process of OLED devices, but also to continuously study and innovate the optoelectronic functional materials in OLED devices to prepare functional materials with higher performance. Based on this, the OLED material industry has been committed to developing new organic electroluminescent materials to achieve low device starting voltage, high luminous efficiency and better device life.
[0005] At present, OLED screen manufacturers widely use the technical means of doping Liq (lithium octahydroxyquinoline) into the ET material layer to achieve low voltage and high efficiency of the device, and to improve the life of the device. The main role of Liq is to reduce a trace amount of metallic lithium under the action of electrons injected by the cathode, thereby playing the role of n-doping the electron transport material, thereby significantly improving the electron injection effect. On the other hand, lithium ions will improve the electron mobility of the ET material through the coordination effect with the N atoms in the electron transport material, so that the Liq-doped ET device has a low operating voltage and high luminous efficiency.
[0006] However, in order to further meet the ever-increasing demand for the optoelectronic performance of OLED devices and the energy-saving needs of mobile electronic devices, it is necessary to continuously develop new and efficient OLED materials, among which the development of new electron transport materials with high electron injection ability and high mobility is of great significance. Summary of the invention
[0007] One of the purposes of the present invention is to provide a compound having good electron injection and migration properties, which can improve the electron injection and migration efficiency of an organic electroluminescent device and obtain the excellent effects of high luminous efficiency and low starting voltage.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] The present invention provides a compound having a structure shown in Formula I;
[0010]
[0011] In Formula I, the X 1 , X 2 and X 3 Each independently selected from CR 1 , CR 2 , CR 3 or any one of N, and at least one of them is N;
[0012] The R 1 , R 2 , R 3 , R 4 , R 5 and R 6Each is independently selected from any one of hydrogen, halogen, cyano, substituted or unsubstituted C1-C12 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, etc.) chain alkyl, substituted or unsubstituted C3-C12 (e.g., C4, C5, C6, C7, C8, C9, C10, etc.) cycloalkyl, substituted or unsubstituted C6-C30 (e.g., C10, C12, C14, C16, C18, C20, C26, C28, etc.) aryl, substituted or unsubstituted C3-C60 (e.g., C4, C6, C8, C12, C15, C18, C20, C23, C25, C28, C30, C36, C40, C46, C48, C50, C54, C58, etc.) heteroaryl;
[0013] In Formula I, m is an integer of 0 to 3, such as 1 or 2; when m is 2 or 3, R 6 Same or different;
[0014] In Formula I, L is selected from any one of a single bond, a substituted or unsubstituted C6-C30 (e.g., C10, C12, C14, C16, C18, C20, C26, C28, etc.) arylene, and a substituted or unsubstituted C3-C30 (e.g., C4, C6, C8, C12, C15, C18, C20, C23, C25, C28, etc.) heteroarylene;
[0015] In Formula I, Ar is selected from any one of C6-C60 (e.g., C8, C12, C15, C18, C20, C23, C25, C28, C30, C36, C40, C46, C48, C50, C54, C58, etc.) aryl substituted with an electron-withdrawing group, and substituted or unsubstituted C3-C60 (e.g., C4, C6, C8, C12, C15, C18, C20, C23, C25, C28, C30, C36, C40, C46, C48, C50, C54, C58, etc.) heteroaryl, and Ar is an electron-withdrawing group;
[0016] When the above groups have substituents, the substituents are each independently selected from halogen, C1-C10 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, etc.) chain alkyl, C3-C10 (e.g., C4, C5, C6, C7, C8, C9, C10, etc.) cycloalkyl, C1-C10 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, etc.) haloalkyl, C2-C10 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, etc.) alkenyl, C1-C6 (e.g., C2, C3, C4, C5, etc.) alkoxy, C1-C6 (e.g., C2, C3, C4, C5, etc.) thioalkoxy, carbonyl, carboxyl, Any one or a combination of at least two of nitro, cyano, amine, C6-C30 (e.g., C8, C12, C15, C18, C20, C23, C25, C28, etc.) monocyclic aromatic group, C10-C30 (e.g., C12, C15, C18, C20, C23, C25, C28, etc.) condensed aromatic group, C3-C60 (e.g., C4, C6, C8, C12, C15, C18, C20, C23, C25, C28, C30, C36, C40, C46, C48, C50, C54, C58, etc.) monocyclic heteroaromatic group, C6-C30 (e.g., C8, C12, C15, C18, C20, C23, C25, C28, etc.) condensed heteroaromatic group. When a "substituted or unsubstituted" group in the present invention has a substituent, the substituent has the above-mentioned selection range, and can be substituted with one group or two or more groups, which will not be described in detail below.
[0017] Formula I compound parent nucleus of the present invention adopts azabenzoindolizine to form, and the N atom on the benzene ring and the N of indolizine group are not in the ortho position, so the weak electron-donating property that indolizine itself has can be balanced, compared with the structures such as single oxazole, thiazole, imidazole, triazole or triazine commonly used in the prior art, the structure of the compound of the present invention has good electron-deficient property, therefore is conducive to the injection of electrons, and has relatively larger planar structure simultaneously, improves electron migration ability, thus is conducive to improving the mobility of the electron of the whole newly constructed molecule. The structural characteristics of the above two aspects can make the whole molecule show good electron injection and migration performance. Therefore, when the compound of the present invention is used as the electron transport layer material in the organic electroluminescent device, the electron injection and migration efficiency in the device can be effectively promoted, thus ensuring that the device obtains the excellent effect of high luminous efficiency, low starting voltage.
[0018] "Electron withdrawing group" in the present invention refers to a group whose electron cloud density on the benzene ring is reduced after the group replaces the hydrogen on the benzene ring, and the Hammett value of such a group is usually greater than 0.6. The Hammett value refers to the characterization of the charge affinity of a specific group, which is a measure of an electron withdrawing group (positive Hammett value) or an electron donating group (negative Hammett value). The Hammett equation is described in more detail in Thomas H.Lowry and Katheleen Schueller Richardson, "Mechanism and Theory In Organic Chemistry', New York, 1987, pp. 143-151, which is cited herein as a reference. Such groups can be listed but are not limited to: triazine, pyrimidine, benzopyrimidine, benzopyridinyl, naphthyridine, phenanthroline, pyrazinyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, pyridazinyl, and the above-mentioned groups substituted with alkyl or aryl.
[0019] Preferably, the compound has the structures shown in (2-1) to (2-6);
[0020]
[0021] The R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , m, L and Ar all have the same meanings as in Formula I.
[0022] The present invention prefers the structures shown in (2-1) to (2-6) above, in which there are 2 to 3 N atoms in total on the parent nucleus. Such a structure is not connected to the N of the indolizine group in the ortho position, which can balance the weak electron-donating property of the indolizine itself. The added 1 to 2 nitrogen atoms will make the overall structural group have stronger electron-withdrawing properties, thereby further improving the electron injection and migration capabilities of the material, improving the luminescence efficiency of the device, and reducing the driving voltage.
[0023] Preferably, the electron withdrawing group includes any one or a combination of at least two of nitro, arylamino, cyano, halogen, phosphorus oxy, carbonyl and acyl, preferably halogen and / or cyano. The C6-C60 aryl group may be substituted with one electron withdrawing group, or may be substituted with two or more electron withdrawing groups at the same time, and the two or more electron withdrawing groups may be the same or different.
[0024] Preferably, Ar is selected from any one of a substituted or unsubstituted triazine group, a substituted or unsubstituted pyrimidinyl group, a substituted or unsubstituted pyridyl group, a substituted or unsubstituted quinazoline group, a substituted or unsubstituted quinoxaline group, a substituted or unsubstituted quinolyl group, a substituted or unsubstituted imidazolyl group, a C6-C20 aryl group substituted with a cyano group, and a C6-C20 aryl group substituted with a halogen.
[0025] Preferably, L is selected from any one of a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted biphenylene group, a substituted or unsubstituted pyridylene group, a substituted or unsubstituted naphthyl group, and a substituted or unsubstituted anthracenyl group.
[0026] Preferably, the R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently selected from any one of hydrogen, phenyl, biphenyl, naphthyl, cyano, halogen, pyridyl, C1-C4 chain alkyl and C3-C6 cycloalkyl.
[0027] Preferably, the compound has any one of the structures shown in A1 to A108 below:
[0028]
[0029]
[0030]
[0031]
[0032]
[0033] A second object of the present invention is to provide an application of the compound described in the first object, wherein the compound is applied to electronic devices.
[0034] Preferably, the electronic device includes an organic electroluminescent device, an optical sensor, a solar cell, a lighting element, an organic thin film transistor, an organic field effect transistor, an organic thin film solar cell, an information tag, an electronic artificial skin sheet, a sheet-type scanner or electronic paper, preferably an organic electroluminescent device.
[0035] Preferably, the compound of one of the objectives is used as an electron transport layer material of the organic electroluminescent device.
[0036] The third object of the present invention is to provide an organic electroluminescent device, comprising a substrate, a first electrode, a second electrode and at least one organic layer located between the first electrode and the second electrode, wherein the organic layer contains at least one compound described in one of the objects.
[0037] Preferably, the organic layer comprises an electron transport layer, and the electron transport layer contains at least one compound described in one of the purposes.
[0038] Specifically, an organic electroluminescent device (OLED) includes a first electrode, a second electrode, and an organic material layer between the electrodes. The organic material can be divided into multiple regions. For example, the organic material layer can include a hole transport region, a light emitting layer, and an electron transport region.
[0039] In a specific embodiment, a substrate may be used below the first electrode or above the second electrode. The substrate is a glass or polymer material with excellent mechanical strength, thermal stability, water resistance, and transparency. In addition, a thin film transistor (TFT) may also be provided on the substrate used as a display.
[0040] The first electrode can be formed by sputtering or depositing a material used as the first electrode on the substrate. When the first electrode is used as an anode, indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO 2 ), zinc oxide (ZnO) and other oxide transparent conductive materials and any combination thereof. When the first electrode is used as a cathode, metals or alloys such as magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-silver (Mg-Ag) and the like and any combination thereof can be used.
[0041] The organic material layer can be formed on the electrode by vacuum thermal evaporation, spin coating, printing, etc. The compound used as the organic material layer can be organic small molecules, organic macromolecules and polymers, and combinations thereof.
[0042] The hole transport region is located between the anode and the light-emitting layer. The hole transport region can be a hole transport layer (HTL) of a single-layer structure, including a single-layer hole transport layer containing only one compound and a single-layer hole transport layer containing multiple compounds. The hole transport region can also be a multi-layer structure including at least one layer of a hole injection layer (HIL), a hole transport layer (HTL), and an electron blocking layer (EBL).
[0043] The material of the hole transport region can be selected from, but not limited to, phthalocyanine derivatives such as CuPc, conductive polymers or polymers containing conductive dopants such as polyphenylene ethylene, polyaniline / dodecylbenzenesulfonic acid (Pani / DBSA), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS), polyaniline / camphorsulfonic acid (Pani / CSA), polyaniline / poly(4-styrenesulfonate) (Pani / PSS), aromatic amine derivatives such as the compounds shown in HT-1 to HT-34 below; or any combination thereof.
[0044]
[0045]
[0046] The hole injection layer is located between the anode and the hole transport layer. The hole injection layer can be a single compound material or a combination of multiple compounds. For example, the hole injection layer can use one or more compounds of HT-1 to HT-34 mentioned above, or one or more compounds of HI-1 to HI-3 below; or one or more compounds of HT-1 to HT-34 can be doped with one or more compounds of HI-1 to HI-3 below.
[0047]
[0048] The light-emitting layer includes a light-emitting dye (i.e., dopant) that can emit light of different wavelength spectra, and may also include a host material (Host). The light-emitting layer may be a monochrome light-emitting layer that emits a single color such as red, green, and blue. A plurality of monochrome light-emitting layers of different colors may be arranged in a plane according to a pixel pattern, or may be stacked together to form a color light-emitting layer. When light-emitting layers of different colors are stacked together, they may be separated from each other or may be connected to each other. The light-emitting layer may also be a single color light-emitting layer that can simultaneously emit different colors such as red, green, and blue.
[0049] According to different technologies, the light-emitting layer material can be made of different materials such as fluorescent electroluminescent materials, phosphorescent electroluminescent materials, and thermally activated delayed fluorescent materials. In an OLED device, a single light-emitting technology can be used, or a combination of multiple different light-emitting technologies can be used. These different light-emitting materials classified by technology can emit light of the same color or different colors.
[0050] In one aspect of the present invention, the light-emitting layer adopts fluorescent electroluminescence technology. The fluorescent host material of the light-emitting layer can be selected from, but not limited to, one or more combinations of BFH-1 to BFH-16 listed below.
[0051]
[0052] In one aspect of the present invention, the light-emitting layer adopts fluorescent electroluminescence technology. The fluorescent dopant of the light-emitting layer can be selected from, but not limited to, one or more combinations of BFD-1 to BFD-12 listed below.
[0053]
[0054] In one aspect of the present invention, the light-emitting layer adopts phosphorescent electroluminescence technology, and the main material of the light-emitting layer is selected from, but not limited to, one or more combinations of GPH-1 to GPH-80.
[0055]
[0056]
[0057]
[0058]
[0059] In one aspect of the present invention, the light-emitting layer adopts phosphorescent electroluminescence technology. The phosphorescent dopant of the light-emitting layer can be selected from, but not limited to, one or more combinations of GPD-1 to GPD-47 listed below.
[0060]
[0061]
[0062]
[0063] Where D is deuterium.
[0064] In one aspect of the present invention, the light-emitting layer adopts phosphorescent electroluminescence technology. The phosphorescent dopant of the light-emitting layer can be selected from, but not limited to, one or more combinations of RPD-1 to RPD-28 listed below.
[0065]
[0066]
[0067] In one aspect of the present invention, the light-emitting layer adopts phosphorescent electroluminescence technology. The phosphorescent dopant of the light-emitting layer can be selected from, but not limited to, one or more combinations of YPD-1 to YPD-11 listed below.
[0068]
[0069] The organic OLED light-emitting device of the present invention includes an electron transport region between the light-emitting layer and the cathode. The electron transport region can be a single-layer electron transport layer (ETL), including a single-layer electron transport layer containing only one compound and a single-layer electron transport layer containing multiple compounds. The electron transport region can also be a multilayer structure including at least one layer of an electron injection layer (EIL), an electron transport layer (ETL), and a hole blocking layer (HBL).
[0070] The electron transport region can also be formed by applying the organic electronic material of the present invention to at least one layer or multiple layers of the structure including an electron injection layer (EIL), an electron transport layer (ETL), and a hole blocking layer (HBL). Of course, the material of the electron transport region can also be a combination of one or more of ET-1 to ET-57 listed below.
[0071]
[0072]
[0073]
[0074]
[0075] The device may also include an electron injection layer located between the electron transport layer and the cathode. The electron injection layer material includes but is not limited to one or more combinations of the following: LiQ, LiF, NaCl, CsF, Li 2 O、Cs 2 CO 3 , BaO, Na, Li or Ca.
[0076] Compared with the prior art, the present invention has the following beneficial effects:
[0077] The parent nucleus of the compound of formula I of the present invention is formed by azabenzoindolizine, and the N atom on the benzene ring and the N of the indolizine group are not in the ortho position, so that the weak electron-donating property that indolizine itself has can be balanced, compared with the structures such as single oxazole, thiazole, imidazole, triazole or triazine commonly used in the prior art, the structure of the compound of the present invention has good electron-deficient property, therefore is conducive to the injection of electrons, and has a relatively larger planar structure simultaneously, improves the electron migration ability, thus is conducive to improving the mobility of the electrons of the newly constructed molecule as a whole. The structural characteristics of the above two aspects can make the molecule as a whole show good electron injection and migration performance. Therefore, when the compound of the present invention is used as the electron transport layer material in the organic electroluminescent device, the electron injection and migration efficiency in the device can be effectively promoted, thus ensuring that the device obtains the excellent effect of high luminous efficiency, low starting voltage. DETAILED DESCRIPTION
[0078] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0079] The representative synthesis route of the compound of formula I of the present invention is as follows:
[0080]
[0081] Various chemicals used in the present invention, such as ethanol, dioxane, toluene, tetrahydrofuran (THF), 2-methyltetrahydrofuran, xylene, toluene, potassium acetate, potassium carbonate, tetrakistriphenylphosphine palladium, 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride, 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl, tris(dibenzylideneacetone)dipalladium(0), and other basic chemical raw materials, are purchased from Shanghai Titan Technology Co., Ltd. and Xilong Chemical Co., Ltd., and some intermediates are purchased from pharmaceutical intermediate manufacturers.
[0082] The following halide intermediates were synthesized on a custom basis from a chemical manufacturer (those skilled in the art can also synthesize according to the above method):
[0083]
[0084] The mass spectrometer used to identify the following compounds was a ZAB-HS mass spectrometer (manufactured by Micromass, UK).
[0085] The following synthesis examples provide the synthesis methods of specific compounds:
[0086] Synthesis example 1:
[0087] Synthesis of Compound A1
[0088]
[0089] Preparation of compound A1-1
[0090] M1 (28 g, 100 mmol), phenylboric acid (14.64 g, 120 mmol), potassium carbonate (41.4 g, 300 mmol) were added to a 500 mL three-necked flask, followed by 280 mL toluene, 40 mL ethanol, and 40 mmol water. After nitrogen replacement three times, tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4, 1.1 g, 1 mmol), and then heated to 110°C for 5 h. TLC showed that the reaction was complete. Toluene was concentrated, water was added and extracted with DCM, the organic phase was collected, and silica gel was added after concentration, and the sample was stirred. Compound A1-1 (17.6 g, yield 63%) was obtained by silica gel column chromatography.
[0091] Preparation of Compound A1
[0092] Compound A1-1 (13.90 g, 50 mmol), potassium carbonate (20.7 g, 150 mmol) and 2-(4-boronic acid pinacol ester)phenyl-4,6-diphenyl-1,3,5-triazine (13.6 g, 50 mmol) were added to a flask containing dioxane: water (200 mL: 40 mL), and tris(dibenzylacetone)dipalladium (Pd 2 (dba) 3 , 0.74g, 1.02mmol) and 2-dicyclohexylphosphine-2',6'-dimethoxybiphenyl (Sphos, 0.74g, 2.04mmol). After the addition is completed, the reaction is stirred and heated under reflux for 8 hours under a nitrogen atmosphere. TLC shows that the reaction is complete. Cool to room temperature and filter the precipitated white solid. Heat reflux with 2L toluene to dissolve, perform vacuum column chromatography and filter, collect the filtrate, concentrate and recrystallize to obtain a white solid compound A1 (14.05g, yield 51%). Molecular weight calculated value: 551.21, measured value C / Z: 551.2.
[0093] Synthesis example 2:
[0094] Synthesis of Compound A3
[0095]
[0096] Preparation of compound A3-1
[0097] M2 (27.9 g, 100 mmol), bipyralidin (30.48 g, 120 mmol), potassium acetate (29.4 g, 300 mmol) and 300 mL of dioxane were added to a 500 mL three-necked flask. After nitrogen replacement three times, palladium acetate (Pd(OAc) 2 , 0.22 g, 1 mmol) and Sphos (0.83 g, 2 mmol), then heated to 120°C for 8 h, TLC showed the reaction was complete. The dioxane was concentrated, water was added and extracted with DCM, the organic phase was collected, concentrated, silica gel was added and stirred, and silica gel column chromatography was used to separate the compound A3-1 (29.6 g, yield 80%).
[0098] Preparation of Compound A3
[0099] Compound A3-1 (18.55 g, 50 mmol), potassium carbonate (20.7 g, 150 mmol) and 2-(3,3-bromobiphenyl)-4,6-diphenyl-1,3,5-triazine (23.15 g, 50 mmol) were added to a flask containing toluene:ethanol:water (200 mL:40 mL:40 mL), and Pd(PPh) was added after nitrogen replacement under stirring at room temperature. 3 ) 4 (1.1 g, 1 mmol). After the addition was completed, the mixture was stirred and heated under reflux for 4 hours under nitrogen atmosphere. TLC showed that the reaction was complete. The mixture was cooled to room temperature and the precipitated white solid was filtered. The mixture was dissolved by heating under reflux with 3 L of toluene, and vacuum column chromatography was performed and filtered. The filtrate was collected, concentrated, and recrystallized to obtain a white solid compound A3 (23.55 g, yield 75%). The calculated molecular weight was 628.24, and the measured C / Z was 628.2.
[0100] Synthesis example 3:
[0101] Synthesis of Compound A10
[0102]
[0103] Compound M3 (9.09 g, 30 mmol), potassium carbonate (12.42 g, 90 mmol) and 2-(4-boronic acid pinacol ester)phenyl-4,6-di(2-pyridyl)-pyridine (13.05 g, 30 mmol) were added to a flask containing tetrahydrofuran:water (200 mL:40 mL), and Pd(PPh 3 ) 4 (1.1 g, 1 mmol). After the addition was completed, the mixture was stirred and heated under reflux for 6 hours under nitrogen atmosphere. TLC showed that the reaction was complete. The mixture was cooled to room temperature and the precipitated white solid was filtered. The mixture was dissolved by heating under reflux with 2 L of toluene, and vacuum column chromatography was performed and filtered. The filtrate was collected, concentrated, and recrystallized to obtain a white solid compound A10 (11.75 g, yield 68%). The calculated molecular weight was 576.21, and the measured C / Z was 576.2.
[0104] Synthesis example 4:
[0105] Synthesis of Compound A18
[0106]
[0107] Preparation of compound A18-1
[0108] M4 (17.84 g, 50 mmol), 2-pyridine boronic acid (7.38 g, 60 mmol), potassium carbonate (20.7 g, 150 mmol) were added to a 500 mL three-necked flask, and then 200 mL of tetrahydrofuran and 40 mL of water were added. After nitrogen replacement three times, tetrakis triphenylphosphine palladium (0.55 g, 0.5 mmol) was added, and then heated to reflux for 5 h. TLC showed that the reaction was complete. The tetrahydrofuran was concentrated, water was added and extracted with DCM, the organic phase was collected, and silica gel was added after concentration to stir the sample, and silica gel column chromatography was used to separate the compound A18-1 (14.77 g, yield 83%).
[0109] Preparation of Compound A18
[0110] Compound A18-1 (10.68 g, 30 mmol), potassium carbonate (12.42 g, 90 mmol) and 3-fluoro-5-(1-naphthalene)-p-biphenylboronic acid (10.26 g, 30 mmol) were added to a flask containing 150 mL of dioxane and 20 mL of water. After nitrogen was replaced under stirring at room temperature, tri(dibenzylideneacetone)dipalladium(0) (0.37 g, 0.05 mmol) and 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl (0.37 g, 1.02 mmol) were added. After the addition was completed, the mixture was stirred and heated under reflux under a nitrogen atmosphere to react until A18-1 reacted completely and the heating was stopped. Naturally cooled to room temperature, the precipitated white solid was filtered. Dissolved by heating under reflux with 1.5 L of xylene, vacuum column chromatography and filtration were performed, the filtrate was collected, concentrated and recrystallized to obtain a white solid compound A18 (9.82 g, yield 55%). Calculated molecular weight: 618.22, measured C / Z: 618.2.
[0111] Synthesis example 5:
[0112] Synthesis of compound A33
[0113]
[0114] Preparation of compound A33-1
[0115] M5 (17.79 g, 50 mmol), 2-pyridine boronic acid (7.38 g, 60 mmol), potassium carbonate (20.7 g, 150 mmol) were added to a 500 mL three-necked flask, and then 200 mL of 2-methyltetrahydrofuran and 40 mL of water were added. After nitrogen replacement three times, tetrakis triphenylphosphine palladium (0.55 g, 0.5 mmol) was added, and then heated to 80 ° C for 7 h. TLC showed that the reaction was complete. 2-methyltetrahydrofuran was concentrated, water was added and extracted with DCM, the organic phase was collected, and silica gel was added after concentration to stir the sample, and silica gel column chromatography was used to separate the compound A33-1 (14.38 g, yield 81%).
[0116] Preparation of compound A33
[0117] Compound A33-1 (10.65 g, 30 mmol) and A33-2 (14.4 g, 30 mmol) were added to a flask containing dioxane: water (150 mL: 20 mL), and potassium carbonate (12.42 g, 90 mmol) was added. After the addition, nitrogen was replaced under stirring at room temperature and Pd 2 (dba) 3 (0.37g, 0.05mmol) and 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (0.41g, 1.02mmol). After the addition is completed, the reaction is stirred and heated under reflux for 8 hours under nitrogen atmosphere. TLC shows that the reaction is complete. Cool to room temperature and filter the precipitated white solid. Heat reflux with 4L toluene to dissolve, perform vacuum column chromatography and filter, collect the filtrate, concentrate and recrystallize to obtain white solid compound A33 (11.91g, yield 59%). Molecular weight calculated value: 673.23, measured value C / Z: 673.2.
[0118] Synthesis example 6:
[0119] Synthesis of Compound A42
[0120]
[0121] Preparation of compound A42-1
[0122] M6 (28 g, 100 mmol) and phenylboric acid (14.64 g, 120 mmol) were added to a 500 mL three-necked flask, and then 280 mL of toluene and 40 mL of ethanol were added to dissolve the mixture. Potassium carbonate (41.4 g, 300 mmol) was weighed and dissolved in 40 mL of water. After nitrogen replacement three times, Pd(PPh 3 ) 4 (1.1 g, 1 mmol), then heated to 110°C for 7 h, TLC showed the reaction was complete. Toluene was concentrated, water was added and extracted with DCM, the organic phase was collected, concentrated, silica gel was added and stirred, and silica gel column chromatography was used to separate compound A42-1 (19.46 g, yield 70%).
[0123] Preparation of Compound A42
[0124] Compound A42-1 (8.34 g, 30 mmol) and A42-2 (14.4 g, 30 mmol) were added to a flask containing dioxane: water (150 mL: 20 mL), and potassium carbonate (12.42 g, 90 mmol) was added. After nitrogen was replaced under stirring at room temperature, tris(dibenzylideneacetone)dipalladium (0) (0.37 g, 0.05 mmol) and Sphos (0.37 g, 1.02 mmol) were weighed. After the addition was completed, the mixture was stirred and heated under reflux for 6 hours under a nitrogen atmosphere. TLC showed that the reaction was complete. Cooled to room temperature, the precipitated white solid was filtered. Dissolved by heating and reflux with 3 L of toluene, vacuum column chromatography and filtration were performed, and the filtrate was collected, concentrated and recrystallized to obtain a white solid compound A42 (11.96 g, yield 62%). Molecular weight calculation value: 623.24, measured value C / Z: 623.2.
[0125] Synthesis Example 7
[0126] Synthesis of Compound A57
[0127]
[0128] Preparation of compound A57-1
[0129] M7 (28 g, 100 mmol), phenylboric acid (14.64 g, 120 mmol), potassium carbonate (41.4 g, 300 mmol) were added to a 500 mL single-mouth bottle, and then 280 mL toluene, 40 mL ethanol, and 40 mL water were added. After nitrogen replacement three times, tetrakistriphenylphosphine palladium (1.1 g, 1 mmol) was added, and then heated to 105 ° C for reaction. The reaction of M7 was detected by TLC. The reaction was stopped and toluene was concentrated, water was added and extracted with DCM, the organic phase was collected, and silica gel was added after concentration to stir the sample, and compound A57-1 (20.29 g, yield 73%) was obtained by silica gel column chromatography.
[0130] Preparation of Compound A57
[0131] Compound A57-1 (8.34 g, 30 mmol), potassium carbonate (12.42 g, 90 mmol) and A57-2 (15.0 g, 30 mmol) were added to a flask containing dioxane: water (150 mL: 20 mL), and tris(dibenzylideneacetone)dipalladium (0) (0.37 g, 0.05 mmol) and 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (0.37 g, 1.02 mmol) were added after replacing nitrogen with stirring at room temperature. After the addition was completed, the mixture was stirred and heated under reflux for 7 hours under nitrogen atmosphere, and TLC showed that the reaction was complete. Cooled to room temperature, the precipitated white solid was filtered. Dissolved by heating and reflux with 4 L of toluene, vacuum column chromatography and filtration were performed, and the filtrate was collected, concentrated and recrystallized to obtain white solid compound A57 (11.52 g, yield 64%). Calculated molecular weight: 600.23, measured C / Z: 600.2.
[0132] Synthesis example 8
[0133] Synthesis of Compound A76
[0134]
[0135] M8 (9.57 g, 30 mmol), potassium carbonate (12.42 g, 90 mmol) and A76-1 (12.24 g, 30 mmol) were added to a flask, 150 mL of dioxane and 25 mL of water were added to the system, and Pd was added after nitrogen replacement under stirring at room temperature. 2 (dba) 3 (0.37 g, 0.05 mmol) and Sphos (0.37 g, 1.02 mmol). After the addition is completed, the reaction is stirred and heated under reflux under nitrogen protection, and TLC detection is performed every 2 hours until the reaction of M8 is complete and then the reaction is stopped. Cool to room temperature and filter the precipitated white solid. Heat reflux with 3L toluene to dissolve, perform vacuum column chromatography and filter, collect the filtrate, concentrate and recrystallize to obtain white solid compound A76 (8.30 g, yield 49%). Molecular weight calculation value: 565.23, measured value C / Z: 565.2.
[0136] Synthesis example 9
[0137] Synthesis of Compound A88
[0138]
[0139] Preparation of Compound A88-1
[0140] M9 (34 g, 100 mmol), o-chlorophenylboric acid (15.6 g, 120 mmol), potassium carbonate (41.4 g, 300 mmol) were added to a 500 mL three-necked flask, followed by 300 mL toluene, 40 mL ethanol, and 40 mmol water. After nitrogen replacement three times, Pd(PPh 3 ) 4 (1.1 g, 1 mmol), then heated to 110°C for overnight reaction, TLC showed that the reaction was complete. Toluene was concentrated, water was added and extracted with DCM, the organic phase was collected, concentrated, silica gel was added and stirred, and silica gel column chromatography was used to separate compound A88-1 (31.62 g, yield 85%).
[0141] Preparation of Compound A88
[0142] Weigh potassium carbonate (12.42 g, 90 mmol), dissolve it in 20 mL of water, add it to a 250 mL round-bottom flask, weigh compound A88-1 (11.16 g, 30 mmol), and 2-(3-boronic acid pinacol ester)phenyl-4,6-diphenyl-1,3,5-triazine (13.0 g, 30 mmol) and add them to the system, then add 150 mL of dioxane, and then add Pd 2 (dba) 3 (0.37 g, 0.05 mmol) and Sphos (0.37 g, 1.02 mmol). Nitrogen was replaced three times, and the reaction was stirred and heated under reflux overnight under nitrogen atmosphere. TLC showed that the reaction was complete. Cooled to room temperature and filtered the precipitated white solid. Dissolved by heating and reflux with 4 L of toluene, vacuum column chromatography and filtration, the filtrate was collected, concentrated and recrystallized to obtain white solid compound A88 (11.03 g, yield 57%). Molecular weight calculated value: 645.23, measured value C / Z: 645.2.
[0143] Synthesis example 10
[0144] Synthesis of Compound A92
[0145]
[0146] Preparation of Compound A92-1
[0147] M10 (30.8 g, 100 mmol) was added to a 500 mL three-necked flask, dissolved in 280 mL toluene, 40 mL of ethanol was added, and then phenylboric acid (14.64 g, 120 mmol) and potassium carbonate (41.4 g, 300 mmol) were weighed and added to the three-necked flask, and 40 mL of water was added to the system. After nitrogen replacement three times, Pd(PPh 3 ) 4(0.56 g, 0.5 mmol), then heated to 108°C to react until M10 reacted completely. Toluene was concentrated, water was added and extracted with DCM, the organic phase was collected, concentrated, silica gel was added and stirred, and silica gel column chromatography was used to separate compound A92-1 (22.7 g, yield 74%).
[0148] Preparation of Compound A92
[0149] Compound A92-1 (9.21 g, 30 mmol), potassium carbonate (12.42 g, 90 mmol) and A92-2 (13.8 g, 30 mmol) were added to a flask containing dioxane: water (150 mL: 20 mL), and Pd was added after nitrogen replacement under stirring at room temperature. 2 (dba) 3 (0.37 g, 0.05 mmol) and Sphos (0.37 g, 1.02 mmol). After the addition was completed, the reaction was stirred and heated under reflux under nitrogen atmosphere overnight. TLC showed that the reaction was complete. Cooled to room temperature and filtered the precipitated white solid. Dissolved by heating under reflux with 3L toluene, vacuum column chromatography and filtration were performed, and the filtrate was collected, concentrated and recrystallized to obtain white solid compound A92 (10.71 g, yield 59%). Molecular weight calculated value: 605.23, measured value C / Z: 605.2.
[0150] Synthesis Example 11
[0151] Synthesis of compound A103
[0152]
[0153] Preparation of Compound A103-1
[0154] M11 (23.94 g, 60 mmol), bipyralidin (19.81 g, 78 mmol), potassium acetate (24.84 g, 180 mmol) and 300 mL of dioxane were added to a 500 mL three-necked flask. After nitrogen replacement three times, 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride (1.31 g, 1.8 mmol) was added and then heated under reflux for overnight reaction. TLC showed that the reaction was complete. The dioxane was concentrated, 1000 mL of DCM was added to dissolve and filtered, the filtrate was collected, concentrated, 250 mL of ethanol was added, heated to 80°C and boiled for half an hour, and then filtered and dried to obtain compound A103-1 (23.33 g, yield 87%).
[0155] Preparation of compound A103
[0156] Compound A103-1 (13.41 g, 30 mmol), potassium carbonate (12.42 g, 90 mmol) and A103-2 (11.46 g, 30 mmol) were added to a flask containing dioxane: water (150 mL: 20 mL), and Pd was added after nitrogen replacement under stirring at room temperature. 2 (dba) 3 (0.37 g, 0.05 mmol) and Sphos (0.37 g, 1.02 mmol). After the addition is completed, the reaction is stirred and heated under reflux under nitrogen atmosphere overnight. TLC shows that the reaction is complete. Cool to room temperature and filter the precipitated white solid. Heat reflux with 3L toluene to dissolve, perform vacuum column chromatography and filter, collect the filtrate, concentrate it, heat reflux with 1000mL of xylene to dissolve, and then naturally cool to room temperature for recrystallization to obtain white solid compound A103 (12.61 g, yield 63%). Molecular weight calculation value: 667.26, measured value C / Z: 667.2.
[0157] Synthesis example 12
[0158] Synthesis of compound A104
[0159]
[0160] Compound M12 (11.49 g, 30 mmol), K 2 CO 3 (12.42 g, 90 mmol) and A104-1 (10.26 g, 30 mmol) were added to a flask containing dioxane: water (150 mL: 20 mL), and Pd was quickly added after nitrogen was replaced under stirring at room temperature. 2 (dba) 3 (0.37g, 0.05mmol) and Sphos (0.37g, 1.02mmol). After the addition is complete, the reaction is stirred and heated under reflux under nitrogen atmosphere overnight. TLC shows that the reaction is complete. Cool to room temperature and filter the precipitated white solid. Heat reflux with 3L toluene to dissolve, perform vacuum column chromatography while hot and filter, collect the hot filtrate, and a large amount of solid precipitates after standing overnight. Filter and rinse the filter cake three times with n-hexane, and vacuum dry to obtain A104 (11.22g, yield 58%). Molecular weight calculated value: 645.29, measured value C / Z: 645.2.
[0161] Example 1
[0162] This embodiment provides an organic electroluminescent device, and the preparation method is as follows:
[0163] The glass plate coated with the ITO transparent conductive layer was ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone:ethanol, baked in a clean environment to completely remove the water, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam;
[0164] Place the glass substrate with the anode in a vacuum chamber and evacuate the chamber to a pressure less than 10 -5 Pa, vacuum evaporating HI-3 as a hole injection layer on the anode layer by a multi-source co-evaporation method, with an evaporation rate of 0.1 nm / s and an evaporation film thickness of 10 nm;
[0165] HT-4 was vacuum-deposited on the hole injection layer as the first hole transport layer of the device, with a deposition rate of 0.1 nm / s and a total deposition thickness of 40 nm;
[0166] Vacuum evaporate HT-14 on the first hole transport layer as the second hole transport layer of the device, the evaporation rate is 0.1nm / s, and the total evaporation film thickness is 10nm;
[0167] The light-emitting layer of the device is vacuum-evaporated on the second hole transport layer. The light-emitting layer includes a main material and a dye material. The evaporation rate of the main material BFH-4 is adjusted to 0.1nm / s by a multi-source co-evaporation method. The evaporation rate of the dye BFD-4 is set at 5%, and the total evaporation film thickness is 20nm.
[0168] ET-17 was vacuum-deposited on the light-emitting layer as the hole blocking layer of the device, with a deposition rate of 0.1 nm / s and a total deposition film thickness of 5 nm;
[0169] An electron transport layer is evaporated on the hole blocking layer by a multi-source co-evaporation method, the evaporation rate of the compound A1 of the present invention is adjusted to 0.1 nm / s, and the ratio of the evaporation rate of ET-57 is set to 100%, and the total evaporation film thickness is 23 nm;
[0170] LiF with a thickness of 1 nm was vacuum evaporated on the electron transport layer (ETL) as the electron injection layer, and an Al layer with a thickness of 80 nm was used as the cathode of the device.
[0171] The difference between Examples 2 to 12 and Comparative Examples 1 to 3 and Example 1 is that Compound A1 is replaced by other compounds, as shown in Table 1 for details.
[0172] The structures of the electron transport materials in Comparative Examples 1 to 3 are as follows:
[0173]
[0174] Among them, D1 and D2 are detailed in patent KR1020190033218A, and D3 is detailed in patent KR1020170111539A.
[0175] Performance Test:
[0176] At the same brightness, the driving voltage and current efficiency of the organic electroluminescent devices prepared in the examples and comparative examples were measured using a PR 750 photoradiometer from Photo Research, a ST-86LA luminance meter (from Beijing Normal University Photoelectric Instrument Factory) and a Keithley 4200 test system. Specifically, the voltage was increased at a rate of 0.1 V per second, and the driving voltage and current efficiency of the organic electroluminescent devices were measured when the brightness reached 1000 cd / m 2 The voltage at this time is the driving voltage, and the current density at this time is measured at the same time; the ratio of brightness to current density is the current efficiency; the performance test results are shown in Table 1.
[0177] Table 1
[0178]
[0179] As can be seen from Table 1, the organic electroluminescent devices of the above-mentioned embodiment and the comparative example are different only in the electron transport material, and the others are the same. The device of the embodiment has higher current efficiency and lower driving voltage than the comparative example, with a current efficiency of 7.86-8.89 cd / A and a driving voltage of 4.59-4.86 V. The reason is speculated to be that the azabenzoindolizine group contained in the compound of the present invention itself has a strong electron-withdrawing ability, which is conducive to the injection of electrons. At the same time, the compound structure in the embodiment mainly consists of two electron-withdrawing groups (azabenzoindolizine parent core and Ar) bridged by L to form an "A-π-A" structure or an "AA" structure, which is conducive to the injection and migration of electrons, thereby improving the efficiency of the device.
[0180] In addition, Ar is connected to the benzene ring side of the azabenzoindolizine through L, which is conducive to achieving a balance between the electron injection and transmission capabilities, avoiding excessive electron injection capability and poor electron transmission capability, which in turn reduces the efficiency of the device.
[0181] In addition, the compound of the present invention has a conjugated group Ar extended and connected at a specific position of the azabenzoindolizine, which can increase the molecular weight on the one hand, so that the glass transition temperature (Tg) and the evaporation temperature meet the device requirements, and on the other hand, it also has good planar conjugation. The structure of the azabenzoindolizine itself has a larger structural plane, which is conducive to the transmission of electrons.
[0182] The electron transport material D1 in Comparative Example 1 contains an electron-donating dibenzofuran group, and the triazine group is connected to the aromatic ring containing N-insulators, which balances the electron-withdrawing property of the triazine group. At the same time, it is connected to the aromatic ring containing N-insulators, which reduces the electron-capturing ability of the material, is not conducive to the injection and migration of electrons, and reduces the device performance.
[0183] The position of the N impurity on the parent core group of the electron transport material D2 in Comparative Example 2 is different from that in the present invention. The presence of two N on the five-membered ring makes the polarity of the molecule too large, which will cause a scattering effect between the migrating electrons and the molecular dipole. It also contains an electron-donating dibenzofuran group, which is not conducive to electron injection and reduces device performance.
[0184] The parent core of the electron transport material D3 in Comparative Example 3 contains only one N atom and an electron-donating carbazole group. The structure as a whole exhibits electron-donating properties, which is also not conducive to electron injection and transport, thereby reducing the performance of the device.
[0185] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A compound, characterized in that The compound has a structure shown in Formula I; In Formula I, the X 1 , X 2 and X 3 are independently selected from any one of CR1, CR2, CR3 or N, and the X 1 , X 2 and X 3 There are 1-2 items in it that are N; The R1, R2, R3, R4, R5 and R6 are each independently selected from any one of hydrogen, halogen, cyano, C1-C10 chain alkyl, C3-C10 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl; In formula I, m is 0 or 1; In Formula I, L is selected from any one of a single bond, a substituted or unsubstituted C6-C20 arylene group, and a substituted or unsubstituted pyridylene group; In Formula I, Ar is selected from any one of a C6-C20 aryl group substituted with an electron-withdrawing group, a substituted or unsubstituted triazine group, a substituted or unsubstituted pyrimidinyl group, a substituted or unsubstituted pyridyl group, a substituted or unsubstituted quinazolinyl group, a substituted or unsubstituted quinoxalinyl group, a substituted or unsubstituted quinolyl group, and a substituted or unsubstituted imidazolyl group, the electron-withdrawing group is any one of a nitro group, a cyano group, a halogen group, or a phosphorus-oxy group, or a combination of at least two of them, and Ar is an electron-withdrawing group; When the above-mentioned groups have substituents, the substituents are independently selected from any one of halogen, C1-C10 chain alkyl, C3-C10 cycloalkyl, C1-C10 haloalkyl, nitro, cyano, C6-C20 monocyclic aromatic group, C10-C20 condensed aromatic group, C3-C20 monocyclic heteroaryl group, C6-C20 condensed heteroaryl group, or a combination of at least two thereof.
2. The compound according to claim 1, characterized in that The compounds have structures shown in (2-1) to (2-3); The R1, R2, R3, R4, R5, R6, m, L and Ar all have the same defined ranges as in claim 1.
3. The compound according to claim 1, characterized in that The compounds have structures shown in (2-4) to (2-6); The R1, R2, R3, R4, R5, R6, m, L and Ar all have the same defined ranges as in claim 1.
4. The compound according to any one of claims 1 to 3, characterized in that The electron withdrawing group is halogen and / or cyano.
5. The compound according to any one of claims 1 to 3, characterized in that The Ar is selected from any one of a substituted or unsubstituted triazine group, a substituted or unsubstituted pyrimidinyl group, a substituted or unsubstituted pyridyl group, a substituted or unsubstituted quinazoline group, a substituted or unsubstituted quinoxaline group, a substituted or unsubstituted quinolyl group, a substituted or unsubstituted imidazolyl group, a C6-C20 aryl group substituted with a cyano group, and a C6-C20 aryl group substituted with a halogen group.
6. The compound according to any one of claims 1 to 3, characterized in that The L is selected from any one of a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted biphenylene group, a substituted or unsubstituted pyridylene group, a substituted or unsubstituted naphthyl group, and a substituted or unsubstituted anthracenyl group.
7. The compound according to any one of claims 1 to 3, characterized in that The R1, R2, R3, R4, R5 and R6 are each independently selected from any one of hydrogen, phenyl, biphenyl, naphthyl, cyano, halogen, pyridyl, C1-C4 chain alkyl and C3-C6 cycloalkyl.
8. A compound, characterized in that The compound has any one of the structures shown in A1 to A108 below:
9. Use of a compound according to any one of claims 1 to 8, characterized in that: The compound is used in electronic devices.
10. The use according to claim 9, characterized in that: The electronic device includes an organic electroluminescent device, an optical sensor, a solar cell, a lighting element, an organic thin film transistor, an organic field effect transistor, an organic thin film solar cell, an information tag, an electronic artificial skin sheet, a sheet-type scanner or an electronic paper.
11. The use according to claim 9, characterized in that: The electronic device is an organic electroluminescent device.
12. The use according to claim 11, characterized in that: The compound is used as an electron transport layer material of the organic electroluminescent device.
13. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises a substrate, a first electrode, a second electrode and at least one organic layer located between the first electrode and the second electrode, wherein the organic layer comprises at least one compound according to any one of claims 1 to 8.
14. The organic electroluminescent device according to claim 13, characterized in that: The organic layer includes an electron transport layer, and the electron transport layer contains at least one compound according to any one of claims 1 to 8.
Citation Information
Patent Citations
Nitrogen-containing compound and organic electronic device using the same
KR1020170111539A
Organic compounds and organic electro luminescence device comprising the same
KR1020190033218A